Measuring determinants of employee satisfaction in an eye hospital: study in India. (1st January 2011) - John, Preethi; Muraleedharan, V.R.; Kamalanabhan, T.J.; Thulasiraj, R.D.
Employee satisfaction is a multi dimensional construct which influences customer satisfaction in the service sector. Very little is known about the facets of employee satisfaction particularly in an eye hospital in the developing world like India. A cross-sectional survey of eye hospital staff namely ophthalmologists, ophthalmic assistants, and support staff using a self-administered questionnaire was carried out in India. This survey was done in two phases. The first phase aimed at understanding the factors which comprises this construct. The second phase aimed at confirming whether the factor structure identified was robust. Towards this end both exploratory and confirmatory factory analysis (CFA) was carried out. Interestingly, the seven dimensions influencing employee satisfaction were seen to be: employee loyalty, employee citizenship, employee empowerment, patient centredness, enabling environment, resource availability and maintenance and role clarity. CFA confirmed the robustness of the structure. Implications of the finding are also discussed.